Digestibility of Ficus roxburghii, Castanopsis indica and Ficus cunia on Growing Buffalo from Western Hills of Nepal - Osti, Netra P.; Chapagain, Purna B.; Tiwari, Megh R.; Upreti, Chet R. (Nepal Agriculture Research Journal, 2014)
Nine buffalo calves were subjected to three fodder tree species namely; Nimaro (Ficus roxburghii), Dhalne Katus (Castanopsis indica) and Rai Khanyu (Ficus cunia) for digestibility trial during November 27 and December 3, 2005 in Regional Agricultural Research Station, Lumle, Kaski, Nepal. Animals were kept 7 days for adaptation for these fodders. Weighed amount of fodder tree leaves including twigs and small branches were fed two times a day and observation on fodder offered, refused and faeces voided were recorded daily. Chemical composition of fresh matter and faeces voided were carried out for dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin, calcium (Ca) and phosphorus (P). The mean DM content and their dry matter digestibility (DMD) of these three fodder tree species were found 27.86, 46.02, 34.72, 73.21, 65.93 and 71.28 percent, respectively. Strong negative correlations (r=-0.75 to –0.78; p<0.05) were observed between Ca and CP with fiber fraction (NDF and ADF). A weak correlation was also observed between P and other constituents with respect to digestibility. From the results, if there could be provision of low fiber content in dry season, the three main nutrients (Ca, P and CP) may easily be absorbed by the animals. Nepal Agric. Res. J. Vol. 9, 2009, pp. 94-98 DOI: http://dx.doi.org/10.3126/narj.v9i0.11646